STRUKTUR DAN DISTRIBUSI PENDAPATAN RUMAH TANGGA PETANI SAWIT POLA KKPA DI DESA BINA BARU KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Frisna Dewi Lestari; Yusmini Yusmini; Susy Edwina (Fakultas Pertanian, Universitas Riau, 2017)
The purposes of this study were: (1) to analyze household income of smallholder oil palm farmers in the Bina Baru village, District Of Kampar Kiri Tengah, (2) to analyze the structure of household income of smallholders farmers in the village Bina Baru District Of Kampar Kiri Tengah, (3) to analyze the distribution of household income smallholders farmers of palm in the village Bina Baru District Of Kampar Kiri Tengah. This research applied survey method. The population in this study was incorporated in the palm farmer groups and samples were taken using proportional random sampling with a total sample of 36 farmers. Sources of revenue largely derived from agricultural products. Agricultural income of the farming sector oil obtained by samples of farmers in the village of Bina Baru was 77.26 %, because oil palm is the main source of income for farmers. There is 9.93 % side income from rubber farming. The distribution of income of smallholder farmers of Bina Baru in the lowest income group of 15 farmers were IDR 1.960.123 – 4.880.095 or 40%. Farmers in the middle income group of 15 farmers were IDR 4.959.824 – 8.441.628 or 40%. While farmers in the highest income group of 6 farmers were IDR 8.912.565 – 12.073.051 or 20%. Gini Ratio index was 0.11 which indicated low inequality and Lorenz curve approaching the perfect evenness. It means that the distribution of household income among the palm farmers is relatively even.